Expectations and motives related to achieving the medical doctor profession and career plans of 6th year students of the Medical Faculty, Pomeranian Medical University (PMU) in Szczecin (part II) - Gąsiorowski, Jakub; Radlińska, Iwona; Pakuła, Aleksandra; Kładna, Aleksandra (Polish Journal of Public Health, 2010)
Introduction. The end of university studies is with a period of reflection, evaluation of studies and crystallization of career plans. The aim of this study was to get to know expectations and motivations related to achieving the medical doctor profession and to career plans of the graduates of the Medical Faculty of PMU.Material and methods. The group of 113 out of total 119 students of the 6th year, the Faculty of Medicine of PMU in the academic year 2004/2005 were asked to complete anonymously a questionnaire during the academic year 2004/2005.Results. The most important motivation to study medi-cine was pointed out by 53.1% of the respondents as “the urge of helping others” , whereas for 42.5% -“the interest in medical subjects and problems” was predominant. Among the most often mentioned (and most important) expectations related to becoming a medical doctor were “possibility to perform a socially important and interesting job” (52.2% of respondents), followed by “certainty of finding a job“ (18.6%) and “possibility of further career development“ (17.7%). Taking into account their future specialization (post-graduate courses), almost ¼ of the respondents have not decided yet. Those who made their decision, most frequently declared specialization in internal diseases (22.1%), gynecology and obstetrics (9.7%) and family medicine (8.0%). The most preferred place for a future career was hospital (61% of respondents). Forty seven percent (47 %) of the respondents plan to work and pursue their professional career in Poland.Conclusions. The crucial reasons of the 6th year students of PMU to study medicine were their internal motivation to help others and their interest in medical subjects. The expectations of the 6th year students of PMU connected with obtaining the profession of a physician correspond with their motivations to study medicine. Working in hospital is perceived by the 6th year students of PMU to be far more attractive than working in primary healthcare.